(untitled) (Journal of Global Humanities and Social Sciences, 2024)
As one of the core elements of Chinese culture, the art of calligraphy carries a rich history and tradition In the contemporary cultural perspective, this paper discusses the artistic function and innovative development path of calligraphy. As an art form, calligraphy demonstrates high aesthetic value, expressing different emotions and artistic styles through various styles of writing and ink. In cultural inheritance, calligraphy, as a form of cultural expression, conveys China’s profound history, culture, and philosophical thought. In international exchanges, calligraphy, as a unique cultural symbol, promotes understanding and respect among different cultures and enhances global awareness of Chinese culture. Attempts to modernize calligraphy, such as its integration with digital technology, have not only injected new vitality into traditional art but also adapted the art of calligraphy to the aesthetic and technological needs of modern society. Together, these artistic functions reflect the unique value and contemporary significance of the art of calligraphy.